2013
DOI: 10.1021/jz402383x
|View full text |Cite
|
Sign up to set email alerts
|

Hot Hole Transfer Increasing Polaron Yields in Hybrid Conjugated Polymer/PbS Blends

Abstract: We use quasi-steady-state photoinduced absorption (PIA) to study charge generation in blends of poly(3-hexylthiophene-2,5-diyl) (P3HT) with PbS nanocrystal quantum dots as a function of excitation energy. We find that, per photon absorbed, the yield of photogenerated holes present on the conjugated polymer increases with pump energy, even at wavelengths where only the quantum dots absorb. We interpret this result as direct evidence for transfer of hot holes in these conjugated polymer/quantum dot blends. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(75 reference statements)
2
24
0
Order By: Relevance
“…Conversely, upon selective excitation of PbS NCs, PIA spectrum of the hybrid composite shows little, if any, P3HT delocalized polaron signal superimposed to PbS NC photo-induced absorption feature (compare black and red spectra in panel a of Figure 6, respectively) implying that hole transfer from PbS NCs to P3HT is hindered. Despite previous reports accounting for NC-to-CP hole transfer, 38,39 a slight contribution of such photo-induced process to the generation of mobile charge carriers in hybrid composites has been argued. 40 In our nanocomposites however, the decay of PbS NC first excitonic peak bleaching is longer in presence of P3HT (Figure 6b), whereas the ground state of P3HT appears as depopulated upon PbS NC selective excitation (Figure 6a and 6c).…”
Section: Photo-induced Processes At the Hybrid Interfacementioning
confidence: 89%
“…Conversely, upon selective excitation of PbS NCs, PIA spectrum of the hybrid composite shows little, if any, P3HT delocalized polaron signal superimposed to PbS NC photo-induced absorption feature (compare black and red spectra in panel a of Figure 6, respectively) implying that hole transfer from PbS NCs to P3HT is hindered. Despite previous reports accounting for NC-to-CP hole transfer, 38,39 a slight contribution of such photo-induced process to the generation of mobile charge carriers in hybrid composites has been argued. 40 In our nanocomposites however, the decay of PbS NC first excitonic peak bleaching is longer in presence of P3HT (Figure 6b), whereas the ground state of P3HT appears as depopulated upon PbS NC selective excitation (Figure 6a and 6c).…”
Section: Photo-induced Processes At the Hybrid Interfacementioning
confidence: 89%
“…have also demonstrated hot‐hole relaxation dynamics in pure CdSe/CdZnS core–shell QDs material with a hot‐hole relaxation time of 7 ps, but they did not place any emphasis on hot‐hole extraction. Recently Strein et al 48. reported non‐thermalized hole transfer in blends of poly(3‐hexylthiophene‐2,5‐diyl) (P3HT)/PbS quantum‐dot composite materials in which the hot‐hole transfer time was not mentioned clearly.…”
Section: Introductionmentioning
confidence: 99%
“…3). Note that for a similar hybrid copolymer-NP system, Ginger et al 37,38 have reported that the transient concentration of the copolymer radical cations does not change significantly with excitation of the NP versus the NP and polymer. Thus, it is likely that hole transfer from (+)NP to (À)PDPPPV is the primary process for the formation of (À)PDPPPV(h).…”
mentioning
confidence: 94%